Chronic excitotoxic lesion of the dorsal raphe nucleus induces sodium appetite - Cavalcante-Lima,H.R. (2005)
We determined if the dorsal raphe nucleus (DRN) exerts tonic control of basal and stimulated sodium and water intake. Male Wistar rats weighing 300-350 g were microinjected with phosphate buffer (PB-DRN, N = 11) or 1 µg/0.2 µl, in a single dose, ibotenic acid (IBO-DRN, N = 9 to 10) through a guide cannula into the DRN and were observed for 21 days in order to measure basal sodium appetite and water intake and in the following situations: furosemide-induced sodium depletion (20 mg/kg, sc, 24 h before the experiment) and a low dose of dietary captopril (1 mg/g chow). From the 6th day after ibotenic acid injection IBO-DRN rats showed an increase in sodium appetite (12.0 ± 2.3 to 22.3 ± 4.6 ml 0.3 M NaCl intake) whereas PB-DRN did not exceed 2 ml (P < 0.001). Water intake was comparable in both groups. In addition to a higher dipsogenic response, sodium-depleted IBO-DRN animals displayed an increase of 0.3 M NaCl intake compared to PB-DRN (37.4 ± 3.8 vs 21.6 ± 3.9 ml 300 min after fluid offer, P < 0.001). Captopril added to chow caused an increase of 0.3 M NaCl intake during the first 2 days (IBO-DRN, 33.8 ± 4.3 and 32.5 ± 3.4 ml on day 1 and day 2, respectively, vs 20.2 ± 2.8 ml on day 0, P < 0.001). These data support the view that DRN, probably via ascending serotonergic system, tonically modulates sodium appetite under basal and sodium depletion conditions and/or after an increase in peripheral or brain angiotensin II.